2016
DOI: 10.1001/jamaoto.2016.3083
|View full text |Cite
|
Sign up to set email alerts
|

Radiotherapy Characteristics and Outcomes for Head and Neck Carcinoma of Unknown Primary vs T1 Base-of-Tongue Carcinoma

Abstract: Intensity-modulated radiotherapy for CUP site or T1-category BOT carcinoma had similar clinical outcomes. Identifying hidden BOT primary carcinoma with novel approaches (eg, transoral robotic surgery and transoral laser microsurgery) may lead to changes in the radiotherapy target volume and dose prescription. Studies are needed to investigate the effect of these differences on quality of life and functional outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 34 publications
1
19
0
2
Order By: Relevance
“…There is a current trend favoring the latter approach as it overcomes surgical complications and allows concomitant treatment of the neck and mucosal sites with the potential index tumor. 54,88 The evidence provided by these two studies, however, should not be overinterpreted as it is hypothesized that HPV-related SCCUP might underline more aggressive disease than HPV-related OPSCC as it is associated with multiple additional genomic alterations. A crucial issue in the management of HPV-related SCCUP is to define whether the radiation field should encompass both sides of the neck and the mucosal axis, which is the subject of an ongoing debate.…”
Section: Discussionmentioning
confidence: 99%
“…There is a current trend favoring the latter approach as it overcomes surgical complications and allows concomitant treatment of the neck and mucosal sites with the potential index tumor. 54,88 The evidence provided by these two studies, however, should not be overinterpreted as it is hypothesized that HPV-related SCCUP might underline more aggressive disease than HPV-related OPSCC as it is associated with multiple additional genomic alterations. A crucial issue in the management of HPV-related SCCUP is to define whether the radiation field should encompass both sides of the neck and the mucosal axis, which is the subject of an ongoing debate.…”
Section: Discussionmentioning
confidence: 99%
“…Although this is the first study to compare a CUP cohort with a matched OPX cohort, other studies suggest that CUP patients have excellent outcomes. Table demonstrates previous studies on CUP and reports outcomes for all patients regardless of HPV status . Most studies are heterogeneous and include patients with unknown HPV status or HPV‐negative disease and then later stratify by HPV status.…”
Section: Discussionmentioning
confidence: 99%
“…This does not seem justified, since a cT1 tumor (in this case not detected, therefore CUP) generally has an excellent prognosis with RT alone [84, 100]. A recent study by Hosni et al revealed an almost identical prognosis for patients with HNCUP and those with T1 base-of-tongue carcinoma [101]. These data would imply that both diseases may be treated the same way, i.e., without the use of chemotherapy.…”
Section: Introductionmentioning
confidence: 99%